EKSPLORASI KREATIVITAS SISWA DALAM SENI ECOPRINT: ANTUSIASME DAN PEMAHAMAN ECOPRINT TEKNIK POUNDING DI KELAS IV SD NEGERI 2 MANYARGADING - M. Khabibun Najib Kurniawan; Nur Fajrie; Ika Oktavianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study explores the creativity of fourth grade students of SD Negeri 02 Manyargading in ecoprint art with pounding technique. Ecoprint, as a method of dyeing fabric using natural materials, encourages students' exploration and creative expression. Through a qualitative approach, this study observed the learning process, student interviews, and documentation of the work. The results showed that although initially unfamiliar, students were enthusiastic about experimenting and creating unique motifs. Constraints in technique and material selection did not hinder their creativity. Ecoprint has proven to be an effective method to foster creativity and introduce environmentally friendly art in elementary schools.